Using GPS and Gravity to Infer Ice Mass Changes in Greenland - VAN DAM, Tonie; Larson, Kristine; Wahr, John; Gross, Susanna; FRANCIS, Olivier (Eos, Transactions American Geophysical Union, 2000)
peer reviewed